The Theoretical Framework of Macroprudential Policy and its Place in the Scheme of Economic Policy - Kálmán, János (Public Governance, Administration and Finances Law Review, 2016)
Microprudential regulation and supervision – focused on institutional risks – cannot guarantee the stability of the financial system. Therefore special attention should be paid to macroprudential regulation and supervision to address systemic risks. The purpose of this study is to provide the historical context and a theoretical framework for macroprudential regulation and supervision – a new area of economic policy. To this end, we shall examine the causes for the spread of macroprudential policy, its basic concepts, and thirdly, its place within the scheme of economic policies.